Estrogenic effect of ethanolic extract of Sambung Nyawa leaves (Gynura procumbens (Lour.) Merr.) in rat - Ika Puspita Sari; Nunung Yuniarti (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2004)
Sambung Nyawa leaves (Gynura procumbens (Lour.) Merr.) has been used traditionally as a cancer medicine especially for ovary cyst and uteri cancer. Previous studies found that ethanolic extract of Sambung Nyawa leaves had asparaginase inhibitor and antiangiogenic activity. This research was done to determine estrogenic effect of ethanolic extract of Sambung Nyawa leaves in rats due to activity in ovary and uteri related to estrogen. Sixty female rats (30 immature rats for uterine weight assay) were grouped into a negative control (group I) namely carboxy methyl cellulose sodium (CMC sodium) 0.1 %, group II as a positive control namely ethynile estradiole in CMC sodium 0.1 %. Group III,IV and V were ethanolic extract of Sambung Nyawa at doses 595, 1445 and 3512.5 mg/kg body weight (bw). Group I to V were administered orally for 3 consecutive days at single dose. Group VI was given ethanolic extract of Sambung Nyawa at dose 595 mg/kg bw for 5 consecutive days at single dose. We determined uterine weight and vaginal cornification as the indicator of estrogenic effect in rats. The results had shown that group II, IV, V and VI increased uterine weight significantly when compared with group I (negative group) such as 85.2 to 306.4 % (p<0.05). Group V and VI had shown an increase of the uterine weight higher than ethynil estradiole (p<0.05).Key words : Sambung Nyawa, the ethanolic extract, uterine weight,